2016
DOI: 10.1073/pnas.1619238114
|View full text |Cite
|
Sign up to set email alerts
|

Congenital myopathy results from misregulation of a muscle Ca2+channel by mutant Stac3

Abstract: Skeletal muscle contractions are initiated by an increase in Ca 2+ released during excitation-contraction (EC) coupling, and defects in EC coupling are associated with human myopathies. EC coupling requires communication between voltage-sensing dihydropyridine receptors (DHPRs) in transverse tubule membrane and Ca 2+ release channel ryanodine receptor 1 (RyR1) in the sarcoplasmic reticulum (SR). Stac3 protein (SH3 and cysteine-rich domain 3) is an essential component of the EC coupling apparatus and a mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
110
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(121 citation statements)
references
References 44 publications
9
110
1
1
Order By: Relevance
“…The functional data strongly support the notion that the STAC3 variants lead to impaired ECC. Indeed, application of KCl caused a small release of sarcoplasmic reticulum Ca 2+ , a result consistent with previous observations in animal models (Cong, Doering, Grange, & Jiang, ; Linsley, Hsu, Groom, et al., ; Nelson et al., ; Polster et al., ). Our results, however, are not fully supportive of previously published data on Ca 2+ release mediated by direct RyR1 activators.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The functional data strongly support the notion that the STAC3 variants lead to impaired ECC. Indeed, application of KCl caused a small release of sarcoplasmic reticulum Ca 2+ , a result consistent with previous observations in animal models (Cong, Doering, Grange, & Jiang, ; Linsley, Hsu, Groom, et al., ; Nelson et al., ; Polster et al., ). Our results, however, are not fully supportive of previously published data on Ca 2+ release mediated by direct RyR1 activators.…”
Section: Discussionsupporting
confidence: 90%
“…As STAC3 has been shown to be a part of the DHPR complex and to stably interact with Ca V 1.1 (Campiglio & Flucher, ; Horstick et al., ; Linsley, Hsu, Groom, et al., ), we hypothesized that the defective ECC in STAC3 patients was a result of impaired binding to Ca V 1.1. Nevertheless, co‐immunoprecipitation of STAC3 with Ca V 1.1 in patient and control muscle samples pulled down STAC3 to equal extent and demonstrated that the protein interaction between STAC3 and Ca V 1.1 was not significantly affected by the STAC3 variants.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of STAC3 is restricted to skeletal muscle, where STAC3 associates with the voltage-gated calcium channel Ca V 1.1 and is involved in mediating voltage-induced calcium release from the sarcoplasmic reticulum (3,4). In nonmuscle cells, STAC3 was shown to facilitate functional membrane expression of Ca V 1.1 and alter the current properties of Ca V 1.2 (5), suggesting a role of STAC proteins as an L-type calcium channel (Ca V 1) regulator.…”
mentioning
confidence: 99%
“…We previously demonstrated that the stable association of STAC3 to the Ca V 1 channel complex in the triads of skeletal muscle relies on the C1 domain (7). In contrast, the NAM mutation, which impairs EC coupling and is located in the SH3-1 domain of STAC3 (2)(3)(4), did not abolish the interaction with the calcium channel (2,4,7). We therefore proposed that STAC3 establishes multiple interactions: one through the C1 domain, responsible for the stable anchoring of STAC3 to the channel, and another one through the SH3-1 domain, involved in EC coupling (7).…”
mentioning
confidence: 99%
“…This species is amenable to genetic manipulation and there is significant conservation in gene sequence and protein function between humans and D. rerio . As a result, human mutant genes are being incorporated into the genomic DNA of D. rerio to examine the molecular basis of disease dysfunction (Ha et al ., ; Buhrdel et al ., ; Bragato et al ., ; Linsley et al ., ). To rapidly screen for the expression of non‐native proteins in the transparent D. rerio embryo, the complementary (c)DNA for green fluorescent protein (GFP) driven by an expression promoter is co‐injected into cells (Long et al ., ; Brion et al ., ).…”
Section: Introductionmentioning
confidence: 98%